2017
DOI: 10.1016/j.aju.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Radical cystectomy in the elderly – Is this a safe treatment option?

Abstract: ObjectiveTo determine if significant differences exist in the perioperative outcomes of patients aged >75 years treated with radical cystectomy (RC) compared to younger patients, as RC is frequently not offered to ‘elderly’ patients with bladder cancer because of supposed increased risks of complications.Patients and methodsWe retrospectively analysed prospectively collected data of all patients that underwent RC in our centre from May 2013 to June 2015. In all, 81 consecutive RCs were identified and included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
(55 reference statements)
2
7
0
2
Order By: Relevance
“…About 20% of all complications were major (Clavien-Dindo Grade 3 or higher) among our patients, which is in line with published data [ 18 ]. In previous analyses, postoperative death rates after cystectomy varied from 0.3% to 7.9%, and we observed similar figures in our series [ 22 , 23 ]. The death rate was the greatest in patients aged ≥ 75 years; however, the overall death rate was low, so our sample was too small to look for predictors of death in multivariable analyses.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…About 20% of all complications were major (Clavien-Dindo Grade 3 or higher) among our patients, which is in line with published data [ 18 ]. In previous analyses, postoperative death rates after cystectomy varied from 0.3% to 7.9%, and we observed similar figures in our series [ 22 , 23 ]. The death rate was the greatest in patients aged ≥ 75 years; however, the overall death rate was low, so our sample was too small to look for predictors of death in multivariable analyses.…”
Section: Discussionsupporting
confidence: 90%
“…For example, Lee et al found no association of age with complication risk among 126 patients after robot-assisted radical cystectomy [ 24 ]. Similarly, other studies did not find a significant relationship between age and the risk of complications of radical cystectomy [ 21 , 23 , 25 ]. Among all the studied clinical factors, we found that only higher ASA scores tended to be associated with a greater risk of major complications (similarly to previous reports) [ 21 , 25 ].…”
Section: Discussionmentioning
confidence: 70%
“…In our previous study, older age alone did not increase the risk of major postoperative complications, prolonged hospital stays, or blood loss among patients who were subjected to radical cystectomy [30]. This concurs with other studies [31][32][33].…”
Section: Discussionsupporting
confidence: 89%
“…Bladder cancer remains the second most common urological malignancy in the world 11 . Radical cystectomy along with pelvic lymphadenectomy, being the gold standard treatment for bladder cancer is performed by the surgeons very frequently.…”
Section: Discussionmentioning
confidence: 99%